REGULASI DALAM PEMBERIAN KREDIT USAHA RAKYAT BAGI USAHA MIKRO, KECIL, DAN MENENGAH - Rismansyah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2025)
Regulation of the Coordinating Minister for Economic Affairs Number 1 of 2023 regulatesthe distribution of People's Business Credit (KUR) by emphasizing the principles of inclusivityand accountability. KUR can be distributed directly by financial institutions or through a linkagepattern in collaboration with other financial institutions to reach a wider range of MSMEs.However, for Indonesian Migrant Workers (PMI), KUR distribution is carried out directly.Distribution through linkage institutions must meet strict technical standards, such as reportingthrough the Program Credit Information System (SIKP), guarantees from verified institutions,and electronic system integration to ensure transparency. Collateral provisions aredifferentiated based on the loan ceiling. For loans below IDR 100 million, additional collateralis not allowed to ensure accessibility. Violations of these provisions are subject to administrativesanctions.The KUR program includes various schemes, including super micro KUR with a ceiling ofup to IDR 10 million and low interest rates, as well as light requirements. The government alsoencourages effective distribution through training for linkage institutions, increased supervision,and information technology support. Intensive socialization to MSMEs, especially in remoteareas, is needed so that they understand the application procedures and their rights.KUR recipients can access other credit as long as the collectibility is smooth, withrestrictions on loan frequency based on sector. Routine reporting to the MSME Financing PolicyCommittee through SIKP is mandatory, and starting October 1, 2023, an integrated electronicsystem will become a mandatory standard. KUR recipients are also directed to participate in theBPJS Ketenagakerjaan program as part of social protection.Overall, the KUR policy aims tostrengthen MSMEs through inclusive, adaptive, and accountable financing, in order to increasethe independence, productivity, and competitiveness of small businesses in Indonesia. Keywords: Regulation, Provision of People's Business Credit